Marco de Trabajo para Construir el Modo Vivo en Distribuciones From Scratch - Gómez, Huriviades Calderón; Lombardo, Miguel Vargas (KnE Engineering, 2018)
The main objective of this research is to develop a framework to build automated scripts that generate the Live mode in the Distributions from Scratch. Special emphasis is placed on the methodology of the initramfs and the use of GNU packages to adequate the scripts to the needs of developers. Moreover, the purpose of this, is to demonstrate the stages involved in developing the scripts and the benefits of running it, based on the results of this research. Keywords: Live-USB Customization, Linux From Scratch, GNU/Linux Custom Distributions, Initramfs, BusyBox